The book of think, or, How to solve a problem twice your size - Burns, Marilyn, 1941-; Weston, Martha (Boston : Little, Brown, 1976)
Provides puzzles, riddles, and projects designed to increase problem solving abilities.
Wilson's Children
Library Journal
Horn Book
5.7
5-8
Keywords: Problem solving; Problem solving -- Problems, exercises, etc; Problem solving